2019
DOI: 10.1051/e3sconf/201912503015
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of Banana Plant (Musa spp.) as Bio-sorbent Materials for Controlling Gaseous Pollutants

Abstract: The use of organic waste as bio-sorbent has been carried out by many researchers in the world. Furthermore, the utilization of plants for treating wastewater is also commonly found in various environmental applications. Nevertheless, a review of the ability of banana plants (Musa spp.) as bio-sorbent to eliminate gaseous pollutants is rarely found and has not been fully understood. In this paper, lignocellulosic biomass from banana plants (bark, stem, leaves, peels, etc) was identified and reviewed. Sorption p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…In Indonesia, several studies have revealed the role banana peels can play in removing polluting gases, such as those from motorized vehicles [23]. Sumiyati [24] have listed potential uses of banana plants for removing gaseous pollutants, including sulfidic acid gas. However, no research has been conducted yet to assess banana plants as bio-adsorbents to remove odors from polluting gases, such as H2S.…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, several studies have revealed the role banana peels can play in removing polluting gases, such as those from motorized vehicles [23]. Sumiyati [24] have listed potential uses of banana plants for removing gaseous pollutants, including sulfidic acid gas. However, no research has been conducted yet to assess banana plants as bio-adsorbents to remove odors from polluting gases, such as H2S.…”
Section: Introductionmentioning
confidence: 99%
“…Musa species is one of the well known plants of the musaeae family that have been used as craft materials [26], packaging materials [27], traditional medicine [28], ingredients in food industry [29], and potential biosorbent in adsorption process [30]. Banana plant as adsorbent of hydrogen sulfide adsorption [31], results of adsorption efficiency found 6.44% on banana peel, 51.83% on its stem, and 76.52% on banana leaves. [32].…”
Section: Introductionmentioning
confidence: 99%